ARRANGEMENT OF AUTHORITIES AND MECHANISM FOR CANCELLATION OF VILLAGE REGULATIONS IN THE FRAMEWORK OF VILLAGE AUTONOMY IN INDONESIA - Eddy Asnawi; Yasrif Yakub Tambusai; Andrew Shandy Utama (JCH (Jurnal Cendekia Hukum), 2021)
Village regulations are statutory regulations established by the village headman after being discussed and agreed with the Village Consultative Body. This study aims to explain the arrangement of authority and the mechanism for canceling village regulations within the framework of village autonomy in Indonesia. The method used in this research is normative legal research, using a statutory approach. Law Number 6 of 2014 concerning Villages regulates the formation of village regulations, but does not regulate the cancellation of village regulations. The cancellation of village regulations is instead regulated in Article 87 of Government Regulation Number 43 of 2014 concerning Implementing Regulations of Law Number 6 of 2014 concerning Villages, which states that village regulations and village head regulations are contrary to the public interest and/or the provisions of laws and regulations that higher is canceled by the regent/mayor. This provision is contrary to Article 9 paragraph (2) of Law Number 12 of 2011 concerning the Establishment of Legislation and is not in accordance with the village autonomy framework as regulated in Law Number 6 of 2014 concerning Villages. The mechanism for canceling village regulations should be carried out through an expanded Village Consultative Body meeting because it is considered to have a sense of justice and the spirit of democracy and is a form of implementation of village autonomy.